Perspectives in physical education - Kroll, Walter P. (Academic Press, 1971)
Perspectives in Physical Education presents a summary of some of the important forces influencing the development of graduate study and research at universities; the origins of professional training for teachers of physical education; and the origins of a scientific or quasi-academic discipline of physical education. The book then discusses the first graduate study programs in physical education and the developments in graduate education. The dimensions of a profession; the research productivity in physical education; and the research laboratory in physical education are also considered. The b.